Fluorescence Imaging of Cell Membrane Potential: From Relative Changes to Absolute Values - Nikolaev, Dmitrii M.; Mironov, Vladimir N.; Shtyrov, Andrey A.; Kvashnin, Iaroslav D.; Mereshchenko, Andrey S.; Vasin, Andrey V.; Panov, Maxim S.; Ryazantsev, Mikhail N. (International journal of molecular sciences, 2023)
Membrane potential is a fundamental property of biological cells. Changes in membrane potential characterize a vast number of vital biological processes, such as the activity of neurons and cardiomyocytes, tumorogenesis, cell-cycle progression, etc. A common strategy to record membrane potential changes that occur in the process of interest is to utilize organic dyes or genetically-encoded voltage indicators with voltage-dependent fluorescence. Sensors are introduced into target cells, and alterations of fluorescence intensity are recorded with optical methods. Techniques that allow recording relative changes of membrane potential and do not take into account fluorescence alterations due to factors other than membrane voltage are already widely used in modern biological and biomedical studies. Such techniques have been reviewed previously in many works. However, in order to investigate a number of processes, especially long-term processes, the measured signal must be corrected to exclude the contribution from voltage-independent factors or even absolute values of cell membrane potential have to be evaluated. Techniques that enable such measurements are the subject of this review.